UZLUKSIZ MAKROSKOPIK TIZIMLARGA OID FIZIKA MASALALARINI YECHISH II. JISMLARNING INERTSIYA MOMENTLARINI HISOBLASH - Yavidov, B.; Abdujamilov, A.; Jumoboyeva, O.; Safarboyeva, F. (SCIENCE and SOCIETY, 2017)
In the article the method of solving tasks on finding of moments of inertia of some macroscopic bodies is considered. There have been shown the calculations of moments of inertia of a simple physical systems as a straight bar, circular ring, circular disk, sphere and solid sphere. Practical application of Steiner theorem is shown too. An alternative method of calculation of moments of inertia of solid sphere is presented. It is stated that the method of solving task has general character and may be used in solving tasks from other parts of physics.